DETERMINAN PERTUMBUHAN EKONOMI DI PROPINSI ACEH - Nujma Faradisi (Signifikan: Jurnal Ilmu Ekonomi, 2015)
This research aims to analyze the effect of own-source revenue, general allocation grant, special allocation fund, and special autonomy fund to economic growth in Aceh district/urban district from 2008 to 2011. To estimate economic growth, this research used the rate of RGDP  growth  for dependent  variable. While own-source revenue, general allocation grant, special allocation fund, and special autonomy funds are research’s  independent  variables.  This study took panel data with Fixed Effect Model (FEM) for the method and seven districts and three urban districts in Aceh Province for the sample. The result shows that economic growth explained by own-source revenue, general allocation grant, special allocation fund, and special autonomy fund by 87,30 percent (Adjusted R2). Then, economic growth able to be effected by own- source revenue, general allocation  grant, special allocation  fund, and  special autonomy fund by 21,64 percent (f-statistic).DOI: 10.15408/sjie.v4i2.2303